FOUNDATIONS OF SECULARITY: GLOBAL EXPERIENCE AND KAZAKHSTAN - SIKHIMBAYEVA, Damira; SHYNGYSBAYEV, Lesken; NURMOLDINA, Inkar (CENTRAL ASIA AND THE CAUCASUS, 2021)
The paper examines the methodological approaches and the conceptual foundations used to assess the degree of secularity in Western political thought. The concepts of secularity and secularism appear and develop due to historical, social, economic and cultural specifics of each particular society, and different factors, social transformations and the changing role of religion in public space among them, revise the content of these concepts.The paper discusses two main trajectories of such changes in the correlations between religion and politics that contributed to the development of secularity models as they are known today. It offers a clear interpretation of the concepts of secularity, the secularity principle, secularism and secularization and an analysis of the main models and interpretations of secularism and the socio-political factors that affect each of the secularity models. The contemporary religious situation and religious politics of Kazakhstan, as well as the political experience of identifying the principles and criteria of secularity in the re- public that synthesizes foreign experience and the specific features of interpretation of secularity inside the country are reflected in the paper.